The National Air Photo Library - Carbonetto, Kim (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1983)
The National Air Photo Library holds more than four million photographs. Complete coverage of the country, including its towns and cities, is available. Many places have been the subject of vertical, oblique, and scenic aerial photography from the beginning of the service in the 1920s.